The effect of ontogeny on estimates of KNM-WT 15000's adult body size. Issue 121 (August 2018) - Cunningham, Deborah L.; Graves, Ronda R.; Wescott, Daniel J.; McCarthy, Robert C.
Abstract: The Homo erectus specimen KNM-WT 15000 has played a critical role in our understanding of body size evolution. New interpretations suggest that KNM-WT 15000 had a younger age-at-death and a more rapid ontogenetic trajectory than previously suggested. Recent fossil discoveries and new interpretations suggest a wide range of body size and shape variation in H. erectus . Based on these new insights, we argue that KNM-WT 15000's adult stature and body mass could have been much smaller than has been traditionally presented in the literature. Using chimpanzee and modern human growth trajectories, we bracketed the range of possibilities for KNM-WT 15000's adult body size between 160.0 and 177.7 cm (5′3″–5′10″) for stature and 60.0 and 82.7 kg (132–182 lbs.) for body mass. These estimates put KNM-WT 15000 near the mean rather than among the largest known H. erectus specimens.